9.7k views
4 votes
Y=-2x+2
y = 7x +11
Solve systems by substitution

User Efrem
by
5.4k points

1 Answer

3 votes

Answer: (-1,4)

Explanation:

y=-2x+2 y=7x+11 <----- substitute this equation for y in the

equation y=-2x+2

7x+11=-2x+2 Add 2x to both sides

9x+11=2 Subtract 11 from both sides

9x=-9 Divide both sides by 9

x=-1

y=-2(-1)+2 Plug in x to one of the equations, I chose y=-2x+2

y=2+2 because it was the easiest, then solve

y=4

Solution is (-1,4)

User Sheneka
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.